Cytokine-induced guanylate binding protein 1 (GBP1) release from human ovarian cancer cells - Carbotti, Grazia; Petretto, Andrea; Naschberger, Elisabeth; Stürzl, Michael; Martini, Stefania; Mingari, Maria Cristina; Filaci, Gilberto; Ferrini, Silvano; Fabbi, Marina (Cancers, 2020)
We showed that IL-27 shares several effects with IFN-γ in human cancer cells. To identify novel extracellular mediators, potentially involved in epithelial ovarian cancer (EOC) biology, we analyzed the effect of IL-27 or IFN-γ on the secretome of cultured EOC cells by mass-spectrometry (nano-UHPLC-MS/MS). IL-27 and IFN-γ modulate the release of a limited fraction of proteins among those induced in the whole cell. We focused our attention on GBP1, a guanylate-binding protein and GTPase, which mediates several biological activities of IFNs. Cytokine treatment induced GBP1, 2, and 5 expressions in EOC cells, but only GBP1 was secreted. ELISA and immunoblotting showed that cytokine-stimulated EOC cells release full-length GBP1 in vitro, through non-classical pathways, not involving microvesicles. Importantly, full-length GBP1 accumulates in the ascites of most EOC patients and ex-vivo EOC cells show constitutive tyrosine-phosphorylated STAT1/3 proteins and GBP1 expression, supporting a role for Signal Transducer And Activator Of Transcription (STAT)-activating cytokines in vivo. High GBP1 gene expression correlates with better overall survival in the TCGA (The Cancer Genome Atlas) dataset of EOC. In addition, GBP1 transfection partially reduced EOC cell viability in an MTT assay. Our data show for the first time that cytokine-stimulated tumor cells release soluble GBP1 in vitro and in vivo and suggest that GBP1 may have anti-tumor effects in EOC.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Guanylate binding protein 1; Interferon-γ; Interleukin-27; Microenvironment; Ovarian cancer; Secretome